Phase II study of mFOLFOX6 in advanced gastric cancer patients with severe peritoneal metastases (WJOG10517G), including an individual patient data comparison with JCOG1108/WJOG7312G - Toshiki Masuishi; Hiroki Hara; Takayuki Ando; Takeshi Kawakami; Yoshiyuki Yamamoto; Naotoshi Sugimoto; Kazuhiro Shiraishi; Taito Esaki; Yuji Negoro; Takao Tsuzuki; Hiroaki Sawai; Masato Nakamura; et al. (Gastric Cancer, 2026)
Abstract Background Advanced gastric cancer patients with severe peritoneal metastases, defined as massive ascites throughout the abdominal cavity and/or inadequate oral intake requiring intravenous infusion support, have been excluded from pivotal clinical trials. Methods This phase II trial evaluated mFOLFOX6 in HER2-negative, chemotherapy-naive advanced gastric cancer patients with severe peritoneal metastases. The primary endpoint was overall survival (OS); secondary endpoints included ascites response rate among patients with massive ascites and oral intake improvement rate. A sample size of 50 was planned to detect a median OS of 9 months, with a threshold of 6 months (one-sided α = 0.05; β = 0.2). A prespecified individual patient data comparative analysis was performed using data from patients treated with 5-fluorouracil/l-leucovorin (FL) or FL plus paclitaxel (FLTAX) in JCOG1108/WJOG7312G. Results Among 51 patients, Eastern Cooperative Oncology Group performance status was 0/1/2 in 3/40/8 patients. Median OS and progression-free survival were 7.4 (lower limit of one-sided 95% confidence interval [CI], 6.5) and 3.8 months, respectively. Among 25 patients with massive ascites, the ascites response rate was 36%. Of 33 patients with inadequate oral intake, 46% achieved improved oral intake. The most frequent grade 3–4 adverse event was neutropenia (51%), and febrile neutropenia occurred in one patient (2%). No treatment-related deaths occurred. In propensity score-weighted analysis, OS hazard ratios with mFOLFOX6 versus FL and FLTAX were 0.76 (95% CI 0.56–1.03) and 0.87 (95% CI 0.64–1.18), respectively. Conclusions mFOLFOX6 was tolerable and may be a treatment option for advanced gastric cancer patients with severe peritoneal metastases. Clinical trial registration jRCTs041180007.